Exploring Brown and Levinson's Politeness Strategies: An Explanation on the Nature of the Politeness Phenomenon - Putri Adrian Sapitri; Aprilia Chasanah; Avivah Adinda Putri; Jessica Paulima (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
This study aimed at reviwing brown levinson politeness strategies purposed in their book (1978) entitled